Agency and its Constraints among Biological Children of Foster Carers. Issue 1 (2nd January 2017) - Roche, Steven; Noble-Carr, Debbie
ABSTRACT: There is currently limited understanding of biological children of foster carers and their experiences of foster care placements. This article presents findings from focus groups with biological children that shed light on their perspectives and experiences. Findings indicate biological children are competent social actors who contribute to, and seek to influence, the care environment in their homes. However, due to a lack of recognition, information, and support, biological children's agency is constrained and their challenges exacerbated. This article argues for increased recognition, information and support for biological children, advocating for a "whole-of-family" approach to foster care practice and policy.